2017
DOI: 10.3389/fpls.2017.01042
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Causes a Reduction in the Biosynthesis of Ascorbic Acid in Soybean Plants

Abstract: Drought provokes a number of physiological changes in plants including oxidative damage. Ascorbic acid (AsA), also known as vitamin C, is one of the most abundant water-soluble antioxidant compound present in plant tissues. However, little is known on the regulation of AsA biosynthesis under drought stress conditions. In the current work we analyze the effects of water deficit on the biosynthesis of AsA by measuring its content, in vivo biosynthesis and the expression level of genes in the Smirnoff-Wheeler pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 58 publications
9
48
0
1
Order By: Relevance
“…Although ascorbic acid has been commonly associated with response to abiotic stress, in this study, we observed a positive relationship of ascorbic acid content with soil moisture availability. This has also been observed in other studies using rice, wheat and soybeans [67][68][69].…”
Section: Discussionsupporting
confidence: 87%
“…Although ascorbic acid has been commonly associated with response to abiotic stress, in this study, we observed a positive relationship of ascorbic acid content with soil moisture availability. This has also been observed in other studies using rice, wheat and soybeans [67][68][69].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the results indicated that Cu NPs application can generate certain stress in tomato plants. This produced an increase in ROS, which activates a defense mechanism [54,62], increasing the production of antioxidant compounds such as ascorbate, glutathione, carotenoids, and flavonoids, among others [64]. The same response has been observed under conditions of mild stress caused by various NPs.…”
Section: Bioactive Compoundsmentioning
confidence: 80%
“…However, Munné-Bosch and Alegre [34] have stated that drought stress caused increased AsA content in chloroplasts but a general reduction of this compound in the leaf tissues of several plant species. Bartoli et al [35] did not find a correlation between drought stress and AsA biosynthesis, although Seminario et al [36] showed that water deficit caused a reduction in the biosynthesis of AsA in soybean. The present research showed that there were differences in the stress duration needed to reduce the content of AsA, which could possibly point to cultivars with improved tolerance to drought.…”
Section: Scoville Heat Units (Shu) Values and Ascorbic Acid (Asa) Conmentioning
confidence: 98%